Examining the Psychometric Properties of the Career Commitment Instrument through Classical Test Theory and the Graded Response Model - Asriadi AM, Muh.; Setiawati, Farida Agus (Journal of Education Reseach and Evaluation, 2023)
The gaps that exist in the literature by conducting a comprehensive evaluation of the psychometric properties of the Career Commitment Instrument using CTT and GRM. This exploratory study aims to analyze the psychometric properties of the career commitment instrument using a classical test theory approach and graded response model. Research using cross-sectional design. Data were obtained from a career commitment questionnaire with 12 statement items and 250 respondents who were randomly selected. The summed ranking method (Likert) was used for scaling, with five response options. Data were analyzed using R Studio's traditional Graded Response Model Theory Test technique. Based on the findings, the quality of the career commitment instrument has an estimated reliability of 0.77 (reliable) and a standard measurement error of 3.3. This instrument has a good Endorsement Index and Discrimination Index, with a classic and modern approach. Furthermore, analysis of the stratified response model revealed that 10 items were suitable and 2 were not. If given to respondents with a low level of ability (θ=-2) to a high level of ability (θ=2), this instrument provides complete information of 58.93 with a standard error of 1.0. This instrument can be used by companies to assess the career commitment of their employees. Future research can test the convergent and divergent validity of the career commitment instrument with similar instruments or with different instruments, to strengthen its validity.